الصفات التشريحية لثلاثة أنواع من جنس النعناع - محمد مفتاح الجروشي; مفيدة عبد الهادي الدبيبة; نوري محمد التاجوري; خالد إسماعيل المدهم (African Journal of Advanced Pure and Applied Sciences, 2024)
This research studied the anatomical characteristics of three species of the genus Mentha, which belongs to the Lamiaceae family (M. longifolia, M. spicata, M. aquatica). The study included the anatomical aspects of the stem and leaves. The anatomical results of the stems and leaves showed a great similarity in the arrangement of the tissues, with collenchyma cells located in the corners inside the stems, in addition to the vascular bundles that appeared in the form of four masses. The species differed in the thickness of the tissues that make up the stem. Cross-sections of the leaves of the two species, M. spicata and M. aquatica, showed that they were bifacial, while M. Longifolia was equal-faced. It also became clear that the pollen grains varied in their shape, being elongated and spherical in water mint and spearmint, and flattened but it was spherical in long-leaf mint, as was the pattern of openings in the species studied, three hexagonal prongs.